2020
DOI: 10.1101/2020.01.18.909416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Reaction-Diffusion Network model predicts a dual role of Cactus/IκB to regulate Dorsal/NFκB nuclear translocation inDrosophila

Abstract: Dorsal-ventral patterning of the Drosophila embryo depends on the NFκB superfamily transcription factor Dorsal (Dl). Toll receptor activation signals for degradation of the IκB inhibitor Cactus (Cact), leading to a ventral-to-dorsal nuclear Dl gradient. Cact is critical for Dl nuclear import, as it binds to and prevents Dl from entering the nuclei. Quantitative analysis of cact mutants revealed an additional Cact function to promote Dl nuclear translocation in ventral regions of the embryo. To investigate this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…For example, Cact degradation on the ventral side of the embryo creates a driving force for a ventrally-directed net flux of Dl/Cact complex, which has the overall effect of shuttling Dl to the ventral side (Carrell et al, 2017). Furthermore, recent experimental and modeling work has suggested that Cact potentiates nuclear translocation on the ventral side of the embryo (Barros et al, 2021;Cardoso et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cact degradation on the ventral side of the embryo creates a driving force for a ventrally-directed net flux of Dl/Cact complex, which has the overall effect of shuttling Dl to the ventral side (Carrell et al, 2017). Furthermore, recent experimental and modeling work has suggested that Cact potentiates nuclear translocation on the ventral side of the embryo (Barros et al, 2021;Cardoso et al, 2017).…”
Section: Discussionmentioning
confidence: 99%